2022
DOI: 10.1155/2022/1434410
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Laparoscopic Cholecystectomy in Patients with Gallbladder Stones with Chronic Cholecystitis

Abstract: Objective. To assess the effectiveness of laparoscopic cholecystectomy in patients with gallbladder stones and chronic cholecystitis. Methods. From July 2018 to January 2020, 90 patients with gallbladder stones and chronic cholecystitis assessed for eligibility were recruited and concurrently assigned (1 : 1) to receive either small-incision cholecystectomy (observation group) or laparoscopic cholecystectomy (experimental group). Outcome measures included operation time, intraoperative bleeding volume, postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…With the advancement in medical sciences and technologies, minimally invasive surgeries have replaced the conventional open surgeries. 6 Cholecystectomies are being performed laparoscopically rather than open methods due to lower risks of wound infection, faster recovery rates, and shorter duration of hospital stays. 7 However, in asymptomatic patients, the added risk of complications including bile duct injury from laparoscopic cholecystectomy must be balanced against the potential benefit of the treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advancement in medical sciences and technologies, minimally invasive surgeries have replaced the conventional open surgeries. 6 Cholecystectomies are being performed laparoscopically rather than open methods due to lower risks of wound infection, faster recovery rates, and shorter duration of hospital stays. 7 However, in asymptomatic patients, the added risk of complications including bile duct injury from laparoscopic cholecystectomy must be balanced against the potential benefit of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The current gold standard treatment for symptomatic gallstone disease is laparoscopic cholecystectomy, which is the minimally invasive procedure for the surgical removal of gallbladder. With the advancement in medical sciences and technologies, minimally invasive surgeries have replaced the conventional open surgeries 6 . Cholecystectomies are being performed laparoscopically rather than open methods due to lower risks of wound infection, faster recovery rates, and shorter duration of hospital stays 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Одним из ярких примеров внедрения технологических усовершенствований в сферу практической медицины является масштабное применение малоинвазивных хирургических вмешательств. Их внедрение в различных областях хирургии как в плановом, так и в экстренном порядке, базирующееся на современных методах визуализации, диссекции и реконструкции целостности биологических тканей минимизировало продолжительность госпитализации и послеоперационную летальность, что в результате позволило значительно улучшить качество медицинского лечения во всех странах мира [6][7][8][9][10][11][12][13]. В настоящее время открытая холецистэктомия продолжает выполняться во многих регионах мира и показана в случаях, если осуществление лапароскопической холецистэктомии невозможно по каким-либо причинам [14][15][16].…”
Section: Introductionunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%